Effectiveness of a Pilot Breastfeeding Educational Intervention Targeting High BMI Pregnant Women - Jacobson, Lisette T. (Kans J Med, 2020)
INTRODUCTION: Overweight and obesity during pregnancy are associated with adverse health outcomes leading to increased maternal and neonatal morbidity and mortality. Women with a high body mass index (BMI) also experience low breastfeeding rates. There is limited evidence of effective educational programs that aim to improve length of breastfeeding among this population. The main objective of this pilot educational intervention was to determine knowledge and skills retention at six weeks after completion of a breastfeeding class. METHODS: A two-hour breastfeeding class was offered during the second and third trimester of pregnancy targeting high BMI women. A longitudinal, survey study design was conducted using two data collection points. No comparator group was employed. RESULTS: Baseline mean age of respondents was 26.6 years (SD = 5.7). Respondents who completed post-intervention surveys were largely white (69.2%) followed by Hispanic (15.4%) and non-Hispanic black (15.4%), some college (57.1%), earned less than $50,000/year (64.3%), had employer-provided insurance (53.8%), and did not receive WIC benefits (78.6%). Most respondents had a pre-pregnancy BMI category of overweight (28.6%) or obese (57.1%). The intervention appeared to have some impact on responses. The following were observed: an increased understanding that baby may be fussy in the evening hours and wants to nurse more often (p < 0.002), how to bring baby to the breast (p = 0.004), knowing what to do if breastfeeding hurts (p = 0.031), and knowing what to do when baby has trouble breastfeeding (p = 0.021). CONCLUSION: Consistent with previous findings, all participants in our study reported increased knowledge to breastfeed. Thus, women’s confidence to breastfeed their infant is enhanced through knowledge obtained from breastfeeding education. Additional studies are underway to assess breastfeeding behaviors.